Tenon Patch Graft in The Management of Corneal Perforations: A case series: Poster Presentation - Case Series - General practitioner - Diba, Amirah Deandra; Martha, Faraby (Majalah Oftalmologi Indonesia, 2023)
Introduction : A full-thickness defect of the cornea that results in a rupture or opening is known as corneal perforation. Despite corneal transplant being the gold standard therapy, finding a donor remains challenging. Tenon patch graft (TPG) may be the alternative surgical procedure to repair the damaged cornea. This case series presents six cases of corneal perforations that have been effectively managed with TPG. Case Illustration : Six cases with corneal perforations in the age range of 6-75 years old were presented with varying perforation sizes ranging from 0.5 to 8 mm. The most common complaints were vision loss, redness, and watery eyes. Ophthalmology examinations revealed five corneal ruptures and one impending corneal rupture caused by trauma, infections, corpus alienum, and post-operative. All patients underwent TPG surgery with compression/infinity sutures using 10-0 nylon, followed by bandage contact lenses, with three adjoined with amniotic membrane transplant. Post TPG, patients were followed up for 1-4 months and no complications such as glaucoma, cataract, or endophthalmitis were found. Discussion : Corneal damage that is not treated promptly causes further erosion of the deeper corneal layers. When medication fails, other measures must be taken to preclude further damage. TPG may be an accessible and cost-effective surgical procedure of choice to preserve eye integrity both functionally and structurally. Conclusion : This case series of tenon patch grafts for corneal perforations less than 9 mm demonstrated the effectiveness of TPG in promoting corneal healing without significant complications. Despite differences in perforation size and patient characteristics, all six cases saw closure of the perforation.